POLICY ANALYSIS OF CORRECTIONAL INSTITUTIONS IN THE JUVENILE CRIMINAL JUSTICE SYSTEM (Normative Study of Law Number 35 of 2014 concerning Child Protection) - Mayang Sari; Widya Timur; Huraira Huraira (JURNAL HUKUM SEHASEN, 2023)
Correctional Institutions (LP) have a central role in the implementation of a fair and equitable criminal justice system, particularly in child protection in accordance with Law No. 35/2014 on Child Protection. This research aims to analyze the policies adopted by correctional institutions in supporting the principles of child protection. In-depth analysis revealed that the law has provided a strong legal basis, but challenges in implementation still exist, such as the lack of resources, limited knowledge of children's rights, and lack of coordination between relevant institutions. Therefore, concrete measures such as intensive training for prison officers, improved access to information, and close collaboration between agencies are needed to overcome these obstacles, with the hope that the criminal justice system will provide better protection for children in conflict with the justice process.